2022
DOI: 10.1021/acs.bioconjchem.2c00126
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Preliminary Evaluation of [68Ga]Ga-NOTA-Insulin as a PET Probe in an Alzheimer’s Disease Mouse Model

Abstract: Aberrant insulin signaling has been considered one of the risk factors for the development of Alzheimer's disease (AD) and has drawn considerable attention from the research community to further study its role in AD pathophysiology. Herein, we describe the development of an insulin-based novel positron emission tomography (PET) probe, [ 68 Ga]Ga-NOTA-insulin, to noninvasively study the role of insulin in AD. The developed PET probe [ 68 Ga]Ga-NOTA-insulin showed a significantly higher uptake (0.396 ± 0.055 SUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Successful application of the modeling method established in this study, will allow us to infer distribution kinetics of other tracers in both health and disease. Indeed, we have employed this approach to evaluate blood-to-brain influx of a newly developed PET probe 68 Ga-NOTA-insulin in wild type and Alzheimer’s transgenic mice (Taubel, Nelson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Successful application of the modeling method established in this study, will allow us to infer distribution kinetics of other tracers in both health and disease. Indeed, we have employed this approach to evaluate blood-to-brain influx of a newly developed PET probe 68 Ga-NOTA-insulin in wild type and Alzheimer’s transgenic mice (Taubel, Nelson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, others have supported this finding, showing inhibition of the BEC insulin receptor did not impact insulin transport in an in vitro model [50] and in mice [48]. In an exciting new paper describing a novel, in vivo insulin PET tracer, co-administration of S961 also had no effect on brain insulin uptake in mice [49]. These data suggest there is another protein(s) responsible for transporting insulin across the BEC.…”
Section: Insulin Bbb Transportmentioning
confidence: 91%
“…There have also been factors and/or states that have had no effect on insulin transport. Most surprisingly, the loss or inhibition of the BEC insulin receptor had no effect on insulin transport [43,[48][49][50]. We have summarized this literature in Table 1 and refer readers to the specific references mentioned for each factor/disease state/intervention investigated.…”
Section: Insulin Bbb Transportmentioning
confidence: 99%
“…Recent studies have found that cerebellar atrophy was associated with insulin resistance and poorer performance on cognitive tests assessing of verbal memory recognition and executive function in older adults with dysglycemia [20]. Moreover, elevated insulin uptake in the cerebellum of Alzheimer's disease rats has been observed [21]. However, it remains unclear whether changes in the cerebellum are related to insulin resistance and how they may further impact the cognitive-emotional functions of T2DM patients.…”
Section: Introductionmentioning
confidence: 99%